2009
DOI: 10.1038/ki.2008.648
|View full text |Cite
|
Sign up to set email alerts
|

Compartmentalization of neutrophils in the kidney and lung following acute ischemic kidney injury

Abstract: During renal ischemia-reperfusion, local and distant tissue injury is caused by an influx of neutrophils into the affected tissues. Here we measured the kinetics of margination and transmigration of neutrophils in vivo in the kidney and lungs following renal ischemia-reperfusion. After bilateral renal injury, kidney neutrophil content increased threefold at 24 h. The neutrophils were found primarily in the interstitium and to a lesser degree marginated to the vascular endothelium. These interstitial neutrophil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
177
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(185 citation statements)
references
References 27 publications
5
177
0
3
Order By: Relevance
“…NGAL from circulating activated neutrophils are primarily reflected in plasma or serum but it can not be ruled out that NGAL from activated neutrophils also contributes to u-NGAL concentrations. During AKI both infiltration of neutrophils in the kidney [38] or glomerular filtration of circulating NGAL may contribute to urinary concentrations of NGAL [39]. The origin of u-NGAL in this setting of elderly but relatively healthy humans is not fully known, however we speculate that a major part of the measured u-NGAL derives from tubular endothelial cells rather than from circulating neutrophils.…”
Section: Discussionmentioning
confidence: 88%
“…NGAL from circulating activated neutrophils are primarily reflected in plasma or serum but it can not be ruled out that NGAL from activated neutrophils also contributes to u-NGAL concentrations. During AKI both infiltration of neutrophils in the kidney [38] or glomerular filtration of circulating NGAL may contribute to urinary concentrations of NGAL [39]. The origin of u-NGAL in this setting of elderly but relatively healthy humans is not fully known, however we speculate that a major part of the measured u-NGAL derives from tubular endothelial cells rather than from circulating neutrophils.…”
Section: Discussionmentioning
confidence: 88%
“…Recruitment of leukocytes, particularly neutrophils and macrophages, is a hallmark of IRI [40][41][42] and both cell types are actively involved in tissue damage in ischemiarelated ARF. 41,43 The impaired leukocyte influx seen in kidneys from both CD47 2/2 mice (and WT mice treated with a CD47 blocking antibody) may be in part as a consequence of reduced proinflammatory cytokine and chemokine levels (particularly CXCL2), and may account for the lower degree of renal dysfunction and tissue damage compared with WT controls.…”
Section: Discussionmentioning
confidence: 99%
“…4 Our group and others have demonstrated the role of different immune cell populations in kidney IRI. [5][6][7][8][9] Recently, an intimate connection between the intestine and the kidneys has been proposed. 10,11 Established data have already shown that modification of microbiota composition could affect the outcome of glomerulopathies, and recent data indicate that renal inflammation is associated with the production of uremic toxins by the intestine and with augments intestinal permeability, leading to the onset of systemic inflammation.…”
mentioning
confidence: 99%